Asuhan Kebidanan Komprehensif Remaja pada Nn “A” dengan Flour Albus - Nur Afifah Harahap; Ardiana Batubara (ITSKES Insan Cendekia Medika Jombang, 2023)
Adolescence is one of the phases in a growth and development process. Adolescent girls have very complex problems, namely reproductive problems related to hormones and reproductive functions, one of which is vaginal discharge. The purpose of this care is to provide comprehensive adolescent midwifery care to Mrs.